Soil data for yield gap assessment and soil suitability index for sustainable intensification - Claessens, Lieven; Cassman, Kenneth G.; Wart, Justin van; Grassini, Patricio; Vanlauwe, Bernard; Ittersum, Martin K. van; Bussel, Lenny G. J. van; Boogaard, H.; Stoorvogel, J.J.; Wolf, Joost; Yang, Haishun (2013)
Providing food and water security for a population expected to exceed 9 billion by 2050 while conserving natural resources requires achieving high yields on every hectare of currently used arable land suitable for intensification. This is especially relevant for sub-Saharan Africa (SSA), where, unlike in other regions of the world, food production is not keeping pace with population growth. While recognizing there are other aspects to food security than production alone (e.g. distribution, demand, waste, governance, population), efficiently increasing production on existing farmland forms an essential component of the sustainable intensification paradigm. In SSA 80% of the food is currently produced by smallholder farmers, and rural population is projected to increase for the next 20 years while average farm size will decrease in most SSA countries. Therefore, smallholder farms must be part of the solution to local and global food security. In agricultural systems with current low yields, there are important opportunities for sustainable intensification through improving ecosystem services and yields simultaneously. However, smallholder production systems across SSA are extremely diverse in terms of agro-ecology (climate, soil, landform) and socio-economic conditions and there is a need for targeting “best fit” approaches from a basket of options, rather than pushing “silver bullet” blanket solutions. Examples of potentially successful options include integrated soil fertility management (ISFM), crop-livestock integration, alternative cropping systems, improved soil and water management, and agroforestry. However, for any of these interventions to be effective, soil quality and responsiveness to improved management is critical because very marginal or degraded soils cannot support intensified systems in a sustainable fashion. Unfortunately degraded and poorly responsive soils cover large areas of Africa and represent the majority of smallholder farmers’ fields in certain regions. Given this situation, a robust, quantitative index to identify and map soils for their suitability to support sustainable intensification is needed. Suitable soils are those that, in their current state, support resource-efficient and cost-effective responses to inputs such as fertilizers and are not prone to erosion, salinization or other forms of degradation that would occur under intensified cropping. In this paper we propose a soil suitability index composed of soil information currently available from the Africa Soil Information Service (AfSIS). The index combines inherent soil properties that are not easily modifiable but important for crop production (e.g. water holding capacity, soil depth) as well as soil attributes that are, in principle, amenable to modification through management and inputs (e.g. soil fertility, pH, and compaction). The index would also include measures of existing soil constraints (e.g. toxicities, salinity, etc). We illustrate the use of the index by combining it with geospatially explicit methodologies for assessing yield gaps that are currently being developed in the Global Yield Gap Atlas project (www.yieldgap.org). We show how this combination can be used to identify areas with climate-soil-cropping systems suitable for sustainable intensification.